Can 18F-FDG PET/CT predict recurrence in patients with cutaneous malignant melanoma? - Kang, S; Ahn, B.-C; Hong, C.M; Song, B.-I; Lee, H.J; Jeong, S.Y; Lee, S.-W; Lee, J; Lee, S.J (Nuklearmedizin - NuclearMedicine, 2011)
The aim of this study was to evaluate the prognostic significance of maximum standardized uptake value (SUVmax) of primary cutaneous malignant melanoma (CMM) lesions by 18F-FDG positron emission tomography/ computerized tomography (PET/ CT) in terms of recurrence. Patients, methods: 37 CMM patients (17 men, mean age: 61.7 ± 13.6 years) that underwent PET/CT at presentation were enrolled in this study. Recurrence was determined by histological confirmation or by radiological and clinical follow- up for at least 8 months after curative surgery. Clinical variables such as age, sex, clinical stage, and primary lesion location, thickness, and ulceration, and SUVmax values were analyzed with respect to their usefulness for predicting recurrence. Results: SUVmax was found to be significantly higher in patients with ulceration of primary lesion of CMM (p = 0.004) and in patients with a stage ≥ III (p < 0.000). Patients that experience recurrence had a significantly higher mean SUVmax value (4.9 ± 2.9) than patients who did not (2.1 ± 1.5, p = 0.024). ROC analysis showed that a SUVmax cut-off value 2.2 had high sensitivity (88.9%) and specificity (67.9%) for predicting recurrence. Kaplan-Meier analysis identified ulceration of primary lesion (p = 0.034), stage ≥ III (p = 0.019) and SUVmax ≥ 2.2 (p = 0.002) as predictors of recurrence. However, Cox proportional-hazards analysis showed that only SUVmax (p = 0.025, relative risk 11.063) significantly predicted recurrence. Conclusion: Preoperative SUVmax of primary lesion was found to be the most potent predictor of recurrence in CMM patient. Patients with high SUV max of primary lesion should be followed meticulously for recurrence.
Keywords: Cutaneous malignant melanoma; 18F-FDG PET/CT; predicting recurrence; standardized uptake value